Bird's eye view the natural world - Farndon, John 1960- (Words & Pictures, 2019)
Get ready for the journey of a lifetime ... up in the sky! Look down from above as you travel around the world on a magical hot-air balloon ride. Float past the misty peaks of China's Guilin Hills, trace the magnificent wildebeest's trek through the African Serengeti, and discover how incredible the natural world can be. Includes three fold-out panoramic views
Keywords: Geography / Juvenile literature; Ecology / Juvenile literature; Natural history / Pictorial works / Juvenile literature; Natural history; Ecology; Géographie / Ouvrages pour la jeunesse; Sciences naturelles / Ouvrages illustrés / Ouvrages pour la jeunesse; Nature; Non-Fiction 7+; Geography; picture books; Picture books; Instructional and educational works; Juvenile works; Illustrated works; Matériel d'éducation et de formation; Livres d'images; Bilderbuch; Sachbilderbuch